Metal‐Free Alkenylation of Salicylaldehydes with Boronic Acids: Synthesis of Skipped Dienes and 2H‐Chromenes. Issue 37 (24th September 2020) - Harris, Dylan H.; Barichello, Renata O.; Bolshan, Yuri
Abstract : Metal‐free alkenylation of salicylaldehydes and the preparation of 2 H ‐chromenes have been developed. Reactions occur in the presence of tetrafluoroboric acid diethyl ether complex. Vinylboronic acid derivatives including indeneboronic acid react readily with salicylaldehydes to afford the corresponding skipped dienes. When 6‐bromo or 6‐chlorosalicylaldehydes are submitted to the reaction conditions the formation of 2 H ‐chromenes is observed in good to excellent yields. Abstract : Short text: The developed methodology allows for a facile preparation of skipped dienes and 2 H ‐chromenes from commercially available starting materials. The reaction between alkenylboronic acids and salicylaldehydes occurs in the presence of an acid catalyst HBF4 · OEt2 .